2020
DOI: 10.1007/s00167-020-06255-3
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic lateral capsule resection is enough for the management of lateral epicondylitis

Abstract: PurposeControversy exists with regards to the etiology and treatment of lateral epicondylitis and the role of the lateral capsule in this pathology. The aim of this study was to compare arthroscopic lateral capsule resection with or without extensor carpi radialis brevis (ECRB) tendon debridement for treatment of lateral epicondylitis. MethodsThis is a retrospective study of 38 patients who underwent arthroscopic surgery for LE with two different techniques: Eighteen patients were treated with arthroscopic lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Previous studies reported successful results with only simple debridement or capsule resection. 23 24) Therefore, incomplete removal of tendinosis may not be an important factor for clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported successful results with only simple debridement or capsule resection. 23 24) Therefore, incomplete removal of tendinosis may not be an important factor for clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 6 , 7 , 24 ] have demonstrated that the radial nerve is prone to injury during the anterolateral approach in elbow arthroscopy. The radial nerve is directly anterior to the radial head, and the anterolateral portal is located anterior to the articulation of the humeroradial joint [ 25 ]. Thaveepunsan et al [ 26 ] reported a needle-and-knife technique for anterolateral portal placement during elbow arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Debridement of the lateral condylar ridge and epicondyle to stimulate a bleeding response at the common extensor origin has shown good results with resolution of lateral epicondylitis symptoms. In addition, lateral capsular resection in isolation has shown promising results for relief of lateral epicondyle symptoms 15 .…”
Section: Methodsmentioning
confidence: 99%
“…Loose body removal, OCD fixation, microfracture, synovectomy, radiocapitellar plica excision, osteophyte excision, and capsular releases are all indications for elbow arthroscopy. Arthroscopic debridement of the common extensor tendon for lateral epicondylitis has also been reported 15 . Contraindications for elbow arthroscopy primarily focus on abnormal anatomic findings.…”
Section: Indications/contraindications For Elbow Arthroscopymentioning
confidence: 99%